SAMPLING TECHNIQUE LOGS: Learning type of sampling technique / Mohamad Aqil Abd Hamid, Nor Akma Shahira Azman and Nurul Hidayana Mohd Noor - Abd Hamid, Mohamad Aqil; Azman, Nor Akma Shahira; Mohd Noor, Nurul Hidayana (2021)
Visualization is one technique of dealing with large volumes of information. Infographics can convey information about a topic more quickly and efficiently rather than plain text. SAMPLING TECHNIQUE LOGS is a set of learning exercises that employs QR codes and online quizzes to provide students, lecturers, and practitioners with a rapid and base knowledge about the sampling approach available in the research field. The main goal of this graphic visual is to improve learners' understanding of sampling techniques and the different types of sampling techniques accessible. Lecturers and students can use innovative ideas as teaching and learning tools. It also helps new students and practitioners, such as researchers in the field of study, by serving as a rapid reference guide. Furthermore, in the period of the Covid-19 pandemic, this innovative idea is believed to make teaching and studying Research courses easier, remembering, and faster, particularly during online distance learning.